Analisis Dampak Penerapan Standar Akuntansi danTeknologi Digital dalam Meningkatkan Kinerja Keuangan Pada KSP Kopdit Sube Huter - Muku, Anjela Maretha Tegu; sanga, Konstantinus pati; jaeng, Wihelmia maryetha Yulia (Jurnal Projemen UNIPA, 2026)
This study aims to analyze the impact of the implementation of accounting standards and digital technology in improving financial performance at the Savings and Loan cooperative KSP. Kopdit Sube Huter. The background of the study is based on the importance of accountable, transparent, and relevant financial reports as a basis for decision-making, especially in Savings and Loan cooperatives that manage member funds. The method used in this study is a qualitative descriptive method with a case study approach. Data were obtained through observation, interviews, and documentation during the internship at KSP. Kopdit Sube Huter. The results of the study indicate that the implementation of accounting standards although still using SAK ETAP and in the transition stage to SAK EP, is able to improve the order and comparability of financial reports. In addition, the use of digital technology through the SIKOPDIT system plays a role in increasing the efficiency of transaction recording, the accuracy of financial data, and the timeliness of financial report preparation. The impact of the implementation of accounting standards and digital technology is reflected in the improvement in the cooperative’s financial performance, as indicated by the growth in the number of members and the increase in Net Operating income (SHU) during the 2021-2024 period. Thus, the implementation of appropriate accounting standards and the synergistic use of digital technology have been proven to contribute positively to the financial performance of KSP. Kopdit Sube Huter.